CI/CD platform for the development of software services - Pinho, Paulo Ricardo Cardoso (2023)
Continuous Integration/Continuous Deployment (CI/CD) platforms are of key importance for the efficient development and delivery of software services. This dissertation presents the design, development and implementation of a CI/CD platform to be implemented in the company Wavecom. The primary objective of this dissertation is to propose a platform with an automated pipeline system, seamless integration with the tools existing in the company, scalability and userfriendliness. To accomplish this objective, three activities were first conducted: several industry-standard tools and platforms were studied and experimented, the existing infrastructure already in place at Wavecom was analysed, and the company’s recommendations from development and DevOps teams were collected. Then, a CI/CD platform was proposed and implemented to automate software releases with streamlined testing and reduce manual intervention. As the number of services that will use this platform are expected to grow in the future, further optimizations to the developed platform are expected due to the nature of each individual requirement.